Analisis Kualitas Layanan Transportasi Umum Lanjutan di Stasiun Kereta Api Tanjung Karang - Tri Nanda Arselia; Sulistyorini, Rahayu; Karami, Muhammad (Universitas Nahdlatul Ulama Blitar, 2026)
In this globalization era, the demand for mobility of people and object are pivotal. The existence of a safe, comfortable, and accessible transportation service should be provided in order to increase demand. This study focuses on the passengers at Tanjung Karang Train Station, where the annual increase in passenger numbers has led to higher demand for post-train transportation services. The research evaluates passengers' satisfaction and perception towards the extension of this service at Tanjung Karang train station using the Servqual method and Importance Performance Analysis method (IPA). Results show 11 negative values (unsatisfactory) and 3 positive values (satisfactory). A Cartesian Diagram is used to show the scale priority in the satisfaction-expectation relationship in 4 different quadrants: 6 variables in Quadrant 1, which requires highest priority improvements, 1 variable in Quadrant 2, which requires performance maintenance, 2 Variables in Quadrant 3, which require low priority, and 5 variables in Quadrant 4 represent over-satisfactory.